The layering construction of the three-dimensional (3D) geological model for Wudalianchi volcanic area, Northeast China - Xue Jiang; Ranran Li (PLoS ONE, 2025)
Establishment of geological model in volcanic area is challenging owing to lack of borehole data and the effect of volcanic activity on rock distribution. Taking full advantage of the existing complete volcanic landforms and recognized for seven eruptive cycles in Wudalianchi volcanic area, here we apply a layered approach to build geological models for meeting rapid development of agriculture and understanding the evolution of regional geological structure. Based on the volcanic eruption cycle, the stratas in Wudalianchi volcanic area are divided into four layers. UGrid (unstructured grid in GMS) is used combining with DEM data to hierarchically build 3D geological structure model of volcanic area, which realize the visualization of regional stratigraphic distribution, and the reliability of the model is verified by the formation mechanisms of different types springs. The stratified modeling provides a scientific and effective mean for the reconstruction of geological structure in volcanic areas where the data are short and the stratigraphic distribution is complex. The 3D geological structure model established can lay a foundation for the prediction, evaluation and sustainable use of regional groundwater, geothermy, mineral water and mineral mud resources.